The City of God Books I & II. - Augustinus, Aurelius sanctus 354-430; Walsh, P. G. (Patrick Gerard) (Oxford Aris and Phillips, 2005)
This edition of Books I & II of "St Augustine's City of God" is the only edition in English to provide a text and translation as well as a detailed commentary of this most influential document in the history of western Christianity. In these books, written in the aftermath of the sack of Rome in AD 410 by the Goths, Augustine replies to the pagans, who attributed the fall of Rome to the Christian religion and its prohibition of the worship of the pagan gods.
Keywords: Augustine, -- Saint, Bishop of Hippo; Apologetics -- Early works to 1800.; Kingdom of God -- Early works to 1800.